Ambivalensi Pengembangan Potensi Wisata: Minimnya Inisiatif dan Kesadaran Masyarakat Lokal Menjadi Motor Penggerak Pengembangan Sungai Aeksiegaon - Wensdy Sitindaon; Elvri Teresia Simbolon; Frainskoy Rio Naibaho; Priska Silaban; Tio Minar Panjaitan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Ambivalensi Pengembangan Potensi Wisata:Minimnya Inisiatif dan Kesadaran Masyarakat Lokal Menjadi Motor Penggerak Pengembangan Sungai Aeksiegaon. The district government's dilemma of watershed development (DAS) is related to management authority. According to the law, watershed management is entirely left to the central and provincial governments. In several districts with rivers, lakes or other water areas, it is difficult to intervene in policies, programs and budget funds for the development of water areas. In this study, the Aeksigeaon river tourist attraction is located right in the middle of Tarutung City. Its strategic position in the middle of the city tends to look neglected and has not managed to become a superior tourist attraction in Tarutung City. Local communities adjacent to the Aeksigeaon river also rarely receive training, tourism development assistance and funding from the District Government. This condition complicates the attraction of the Aeksigeaon river because there is no presence from the local community, local government or private sector that specifically manages it optimally. This study emphasizes that the empowerment of local communities can be a driving force for developing Aeksigeaon river tourism objects. This study uses qualitative research with data collection through interviews and direct observation with local communities, traders and related government agencies.